Unilateral pulmonary agenesis associated with colloidal goiter in a newborn: a case report - Gökhan, Güzide Ayşe; Ozbilim, Gülay; Bozova, Sevgi; Güra, Aşkin; Ongun, Hakan; Mihci, Ercan; Arslan, Gökhan (The Turkish Journal of Pediatrics, 2005)
Unilateral pulmonary agenesis is a very rare developmental malformation that is often associated with other anomalies. It can be asymptomatic or present with respiratory symptoms. Our case is a female newborn infant who had been taken to the hospital suffering from difficulty in breathing at the first day of birth. The baby died at the age of three days due to respiratory failure. On autopsy examination and its histopathological evaluation, we detected right pulmonary agenesis and colloidal goiter. According to the literature, pulmonary agenesis is associated with other anomalies including esophageal atresia, tracheal stenosis, musculoskeletal anomalies, DiGeorge syndrome and cardiovascular malformations such as septal defects, patent ductus arteriosus and total anomalous pulmonary venous return. To our knowledge, this is the first case of pulmonary agenesis associated with colloidal goiter.